Individual‐based measurements of light intensity provide new insights into the effects of artificial light at night on daily rhythms of urban‐dwelling songbirds. (30th October 2013) - Dominoni, Davide M.; Carmona‐Wagner, Esther O.; Hofmann, Michaela; Kranstauber, Bart; Partecke, Jesko; Verhulst, Simon
Summary The growing interest in the effects of light pollution on daily and seasonal cycles of animals has led to a boost of research in recent years. In birds, it has been hypothesized that artificial light at night can affect daily aspects of behaviour, but one caveat is the lack of knowledge about the light intensity that wild animals, such as birds, are exposed to during the night. Organisms have naturally evolved daily rhythms to adapt to the 24‐h cycle of day and night, thus, it is important to investigate the potential shifts in daily cycles due to global anthropogenic processes such as urbanization. We captured adult male European blackbirds (Turdus merula) in one rural forest and two urban sites differing in the degree of anthropogenic disturbance. We tagged these birds with light loggers and simultaneously recorded changes in activity status (active/non‐active) through an automated telemetry system. We first analysed the relationship between light at night, weather conditions and date with daily activity onset and end. We then compared activity, light at night exposure and noise levels between weekdays and weekends. Onset of daily activity was significantly advanced in both urban sites compared to the rural population, while end of daily activity did not vary either among sites. Birds exposed to higher amounts of light in the late night showed earlier onset of activity in the morning, but light at night did not influence end of daily activity. Light exposure at night and onset/end of daily activity timing was not different between weekdays and weekends, but all noise variables were. A strong seasonal effect was detected in both urban and rural populations, such as birds tended to be active earlier in the morning and later in the evening (relative to civil twilight) in the early breeding season than at later stages. Our results point at artificial light at night as a major driver of change in timing of daily activity. Future research should focus on the costs and benefits of altered daily rhythmicity in birds thriving in urban areas.